Parties in Civil Lawsuits According to Provisions of Legislation on Civil Procedure of Serbia from 1865 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The article sheds light on provisions of Code of Civil Procedure from 1865 concerning parties in civil lawsuits. Beside plaintiff and defendant, position of third parties in litigation such as intervener, guardian of a minor or an adult deprived of legal capacity, as well as of legal representative (i.e. attorney) was also carefully scrutinized in this paper. As being fully aware of their significance, the author of the Code, minister of justice Rajko Lešjanin dedicated 33 paragraphs to parties in civil lawsuits. They had been very attentively drafted after thorough and detailed discussion between the author of the draft and the State Council′s Commission. Legal capacity of litigants and their representation before courts of law is especially meticulously regulated. Aforementioned provisions (except for paragraph 65 that was somewhat revised in 1900) remained intact during the whole period that the Code was in force. Minister of justice Stojan Novaković, however, in his draft from 1872 proposed amendments and supplements to the two articles regarding the course of time during which intervener should be allowed to join ongoing litigation and ability of parties in lawsuit to appoint more than one legal representative but, since Novakovićʹs document was never enacted, these articles were left unrevised.